Finite element solution of mixed convection micropolar fluid flow between two vertical plates with varying temperature - Kumar, L.; Bhargava, R.; Bhargava, P.; Takhar, H.S. (Archives of Mechanics, 2005)
This paper presents a finite element solution for the mixed convection micropolar fluid flow between two parallel plates with varying temperature. The governing differential equations are solved numerically using the finite element method. The effect of important parameters, namely pressure gradient, micropolar parameter and surface, condition parameter on velocity, microrotation as well as on temperature functions has been studied. It is noticed that the micropolar fluids act as a cooling agent as well as a drag reducing fluids.